2005
DOI: 10.1042/bj20050480
|View full text |Cite
|
Sign up to set email alerts
|

The functioning of mammalian ClC-2 chloride channel in Saccharomyces cerevisiae cells requires an increased level of Kha1p

Abstract: The mammalian chloride channel ClC-2 is a member of the CLC voltage-gated chloride channels family. This broadly expressed protein shows diverse cellular locations and despite numerous studies, its precise function is poorly understood. Disruption of ClC-2-encoding gene in mouse leads to retinal and testicular degeneration and mutations in CLC2 (gene encoding the ClC-2 channel) are associated with idiopathic generalized epilepsies. ClC-2 may also be responsible for Cl- transport in mouse salivary glands. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…A pre-vacuolar-bound Na ϩ /H ϩ antiporter (Nhx1p) mediates cation/H ϩ exchange in prevacuoles and possibly in other intracellular compartments (12,16). More recently, a K ϩ /H ϩ exchanger (Kha1p) at the Golgi was reported, and its role in pH regulation was postulated (10,11). Although in S. cerevisiae, vacuolar Na ϩ (and K ϩ ) transport has been attributed mainly to Nhx1p (14), our data and other reports (18,19) Our results clearly indicated that Vnx1 mediated Na ϩ , K ϩ , and Li ϩ transport into the vacuole and that the lack of Vnx1p increased the salt sensitivity of the cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pre-vacuolar-bound Na ϩ /H ϩ antiporter (Nhx1p) mediates cation/H ϩ exchange in prevacuoles and possibly in other intracellular compartments (12,16). More recently, a K ϩ /H ϩ exchanger (Kha1p) at the Golgi was reported, and its role in pH regulation was postulated (10,11). Although in S. cerevisiae, vacuolar Na ϩ (and K ϩ ) transport has been attributed mainly to Nhx1p (14), our data and other reports (18,19) Our results clearly indicated that Vnx1 mediated Na ϩ , K ϩ , and Li ϩ transport into the vacuole and that the lack of Vnx1p increased the salt sensitivity of the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Kha1p has been described as a putative K ϩ /H ϩ antiporter, and its deletion induced a growth defect at high external pH and hygromycin (10). Kha1p co-localized with Mntp1p, a Golgi-specific marker (11). Although Kha1p displays high amino acid sequence similarity to other Na ϩ /H ϩ antiporters, its ability to mediate K ϩ /H ϩ exchange has not been yet demonstrated.…”
mentioning
confidence: 99%
“…Although this family of proteins has been identified from many organisms ranging from bacteria to humans (13,(15)(16)46), the physiological role of Kha1p has not been defined. Previous studies suggested that Kha1p might serve as a K ϩ efflux transporter (47), which localized to the Golgi (48,49) or mitochondria (50). Cells expressing Kha1p fused with RFP (Kha1p-RFP) display fluorescence associated with vesicle-like compartments (Fig.…”
Section: Kha1p Is a New Molecular Factor Involved In Respiratory Growmentioning
confidence: 94%
“…Among the three yeast Na ϩ /H ϩ antiporters, Kha1 (encoded by YJL094c) has the highest level of similarity to bacterial sodium or potassium/proton antiporters (218,227). Although for some time it was believed to be a plasma membrane transporter (227), later it was shown to reside in the membrane of the Golgi apparatus (78,153). Deletion of KHA1 results in a growth defect in media with high pH or containing hygromycin B.…”
Section: Endosomes and Golgi Apparatusmentioning
confidence: 99%
“…There is no direct evidence regarding the substrate specificity of Kha1, but potassium is most probably its substrate, as the inability of the kha1⌬ mutant to grow at higher pH can be suppressed by the addition of moderate concentrations of KCl (78,153). Similar to the case for the other yeast intracellular alkali metal cation/H ϩ antiporters, Kha1 is believed to be involved in the regulation of intraorganellar potassium and pH homeostasis and most probably acts in collaboration with the Gef1 anion channel, as high cellular levels of Kha1 are required for the functional expression of a mammalian ClC-2 channel in S. cerevisiae and for complementation of the gef1⌬ phenotype (78).…”
Section: Endosomes and Golgi Apparatusmentioning
confidence: 99%